2003
DOI: 10.1523/jneurosci.23-20-07470.2003
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of Glucose Metabolism in the Regulation of Inducible Nitric Oxide Synthase Gene Expression in Glial Cells: Possible Role of Glucose-6-Phosphate Dehydrogenase and CCAAT/Enhancing Binding Protein

Abstract: In rat glial cells the lipopolysaccharide (LPS)-induced inducible nitric oxide synthase (iNOS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 42 publications
4
32
0
Order By: Relevance
“…The direct effect of glucose availability on inflammatory response at the cellular level has been described. LPS-induced NO/iNOS induction was increased at high glucose-cultured cells than normal glucose-cultured cells via enhancing activation of NF-B (30,38,39). We newly propose in this report that glucose availability sensed by HBP flux influences the regulation of inflammation.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The direct effect of glucose availability on inflammatory response at the cellular level has been described. LPS-induced NO/iNOS induction was increased at high glucose-cultured cells than normal glucose-cultured cells via enhancing activation of NF-B (30,38,39). We newly propose in this report that glucose availability sensed by HBP flux influences the regulation of inflammation.…”
Section: Discussionmentioning
confidence: 53%
“…Among these transcriptional factors, C/EBP-␦ may be a critical mediator in glucose-mediated regulation of iNOS gene expression in response to LPS (39). We found that C/EBP-␦ protein expression was reduced as the glucose concentration increased with or without LPS.…”
Section: Discussionmentioning
confidence: 73%
“…Cell viability was determined using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assays as described previously (50). BV2 microglia proliferation was measured by BrdU incorporation assay.…”
Section: Cell Viability and Proliferation Assaymentioning
confidence: 99%
“…Although most of the studies related to manipulation of iNOS promoter have been performed in non-CNS cells, a few studies have also registered the activation of iNOS promoter in mouse and rat glial cells (13,106,117,143). In recent past, our lab has mainly concentrated on the activation of human iNOS promoter in human U373MG astroglial cells and primary astrocytes.…”
Section: Transcriptional Regulationmentioning
confidence: 99%